2020
DOI: 10.1128/jvi.02183-19
|View full text |Cite
|
Sign up to set email alerts
|

Palmitoylated Cysteines in Chikungunya Virus nsP1 Are Critical for Targeting to Cholesterol-Rich Plasma Membrane Microdomains with Functional Consequences for Viral Genome Replication

Abstract: In mammalian cells, alphavirus replication complexes are anchored to the plasma membrane. This interaction with lipid bilayers is mediated through the viral methyl/guanylyltransferase nsP1 and reinforced by palmitoylation of cysteine residue(s) in the C-terminal region of this protein. Lipid content of membranes supporting nsP1 anchoring remains poorly studied. Here, we explore the membrane binding capacity of nsP1 with regard to cholesterol. Using the medically important chikungunya virus (CHIKV) as a model, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 74 publications
1
31
0
1
Order By: Relevance
“…CHIKV nsP3 was proposed to be involved in spherule assembly by recruiting BIN1/amphiphysin 2, an F-BAR protein involved in membrane curvature, but there is still a lack of clear evidence (92) (Figure 3). Furthermore, the contribution of defined membrane lipid species should be considered with a special attention to fatty acid molecular species that determine the fluidity or curvature of the lipid bilayer, depending on the length and saturation of their fatty acyl chains, and to negatively charged phospholipids and cholesterol that regulate nsP1 capping activity and membrane affinity, respectively (74,93), and could alternatively promote host cofactor coalescence to the replication site to assist spherule assembly.…”
Section: Building Membrane Spherules To Ensure Viral Replicationmentioning
confidence: 99%
“…CHIKV nsP3 was proposed to be involved in spherule assembly by recruiting BIN1/amphiphysin 2, an F-BAR protein involved in membrane curvature, but there is still a lack of clear evidence (92) (Figure 3). Furthermore, the contribution of defined membrane lipid species should be considered with a special attention to fatty acid molecular species that determine the fluidity or curvature of the lipid bilayer, depending on the length and saturation of their fatty acyl chains, and to negatively charged phospholipids and cholesterol that regulate nsP1 capping activity and membrane affinity, respectively (74,93), and could alternatively promote host cofactor coalescence to the replication site to assist spherule assembly.…”
Section: Building Membrane Spherules To Ensure Viral Replicationmentioning
confidence: 99%
“…HIV-1 glycoprotein palmitoylation is required for gp160 incorporation and infectivity [ 148 ]. Alphavirus TF (transframe) protein is palmitoylated and is involved in its localization to the plasma membrane and incorporation into a virus [ 149 ], and palmitoylated nsP1 is involved in anchoring replication complex to the plasma membrane [ 154 ]. The examples mentioned above show that the palmitoylation of viral proteins is crucial for viral replication.…”
Section: Lipidationmentioning
confidence: 99%
“…The middle part of nsP1, spanning amino acid residues 245 to 264, contains an amphipathic helix responsible for association of the alphavirus replication complex (RC) with membranes ( 49 ). Specifically, the presence of amphipathic helix and palmitoylated cysteines 417 to 419 ( 50 ) allows nsP1 and nsP1-containing replication complexes to anchor to cholesterol-enriched membrane microdomains ( 51 ). Importantly, site-directed mutagenesis of conserved residues in alphavirus nsP1 indicated that abrogation of nsP1 enzymatic activities is detrimental for virus replication ( 52 ).…”
Section: Nonstructural Protein 1 (Nsp1)mentioning
confidence: 99%